Technology Entrepreneurship Project (ENT 600) : Panasonic Malaysia Sdn Bhd / Nurul Nadhirah Hasrodi - Hasrodi, Nurul Nadhirah (2021)
Panasonic Sdn Bhd is a company that produce variety types of household appliance products. In this study focus to one product which is steam iron. Even this product use many technology to make this product suitable to everyone it is still have problems. The main purpose of this study is solve the problem from technology Panasonic and also to suggest recommendation to the company in order to improve their products and company in future. The first problem regarding their product is product need recharge. As we know, with charged it will caused highest cost to pay bills and not durable which is steam iron can stay longer for 6 to 8 hours only. The other problems for this product is steam iron can use for specific fabrics. Steam iron are not effective to polyester blend fabric or wool, but steam iron can work best on cotton and line. Therefore, this study will come out with three alternative for this two problems. The alternative for first problem is improve durability products, do some innovation and increase market strategy. For other issues which is specific fabrics, the alternative is do some research, make innovation and friendly fabrics. Finally, after we analyzing and examining the problems, only one major problem we choose and give the best alternative for this products. The major problem for Panasonic steam iron is need recharge. The recommendation to this problems is make innovation for steam iron with using durable battery. In conclusion, to finding the weakness and product problems, I was able to issue some suggestion to fix the problems faced by Panasonic company